RANCANG BANGUN JARINGAN FIBER OPTIK SEBAGAI INFRASTRUKTUR INTERNET CEPAT DALAM MENDUKUNG AKTIVITAS DIGITALISASI UMKM DI DESA KOTA PARI - Wadly, Fachrid; Fitriani, Wirda; Muslim, Muslim (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2023)
The use of internet and communication technology is very important in today's digital era, especially in supporting the digitization of UMKM in the Kota Pari Village area where the village is one of the villages that has great potential in developing UMKM, but slow internet access is often an obstacle. Therefore, this study aims to design and build a fiber optic network as a fast internet infrastructure to support UMKM digitalization activities in Kota Pari Village. The research method used in this study is an experimental method using fiber optic network design. The advantage of using this fiber optic network is that it can increase fast and affordable internet access, as well as support digitalization activities for UMKM in Kota Pari Village which can contribute to local economic development in the Kota Pari Village area. The fiber optic network infrastructure that will be built can provide a fast and stable internet connection for UMKM to increase their productivity and business quality, as well as expand market reach through digital platforms. In the construction of this fiber optic network, although there are still obstacles in its construction, this can be overcome with the support of the government and related stakeholders. Therefore, the application of fiber optic network technology as a fast internet infrastructure needs to be continuously optimized as a solution to increase internet access in rural areas, especially in Kota Pari Village.